2009 Eighth Mexican International Conference on Artificial Intelligence 2009
DOI: 10.1109/micai.2009.15
|View full text |Cite
|
Sign up to set email alerts
|

Towards a set of Measures for Evaluating Software Agent Autonomy

Abstract: Abstract-Agent-oriented software is an established research field. For this reason, it is important to develop comprehensive measures of excellence to evaluate this software. No set of measures defining the overall quality of an agent has been developed to date. Some attempts at evaluating agent quality have addressed certain agent features, like the development process. We believe that agent quality can be determined as a function of well-defined characteristics. Evaluated using appropriate measures, these ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
20

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 10 publications
0
17
0
20
Order By: Relevance
“…This step should be followed by the proposition of metrics in order to measure, objectively, the complexity of the developed MAS. According to Alonso et al [13], the measurement of metrics in MAS field is closely dependent on the implementation paradigm used to develop this system. Because the MAS can be implemented using various software paradigms (object-oriented paradigm, knowledge-base systems, etc), it seems hard difficult to propose adequate metrics for all these software paradigms.…”
Section: Measuring the Complexity Of Multi-agent Systemsmentioning
confidence: 99%
“…This step should be followed by the proposition of metrics in order to measure, objectively, the complexity of the developed MAS. According to Alonso et al [13], the measurement of metrics in MAS field is closely dependent on the implementation paradigm used to develop this system. Because the MAS can be implemented using various software paradigms (object-oriented paradigm, knowledge-base systems, etc), it seems hard difficult to propose adequate metrics for all these software paradigms.…”
Section: Measuring the Complexity Of Multi-agent Systemsmentioning
confidence: 99%
“…[7] [10] Agent autonomy is a characteristic that is interpreted as freedom from external intervention, oversight, or control. Autonomous agents are agents that are able to work on behalf of their user without the need for any external guidance.…”
Section: A Software Agent and Its Properties[1]mentioning
confidence: 99%
“…Measuring software quality of an agent depends upon the ability to describe the agent characteristics such as autonomy, reactivity, proactiveness and collaboration. A set of measures for evaluating the software agent's autonomy [6] [9], pro-activity [7], socialability [8] [9], has been dealt in the literature. In this paper, a set of measures for evaluating the software agent's reactivity property, considering its associated attributes has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the characteristic of software agent proactivity, we propose, based on our experience with software agents [5], [6] and the existing research [7], [14], that it should be identified by three attributes:…”
Section: Pro-activity and Its Attributesmentioning
confidence: 99%
“…Early results measuring software agent social ability and autonomy characteristics were presented in [5], and [6], respectively. This paper presents a set of measures for evaluating a software agent's pro-activity, considering its associated attributes.…”
Section: Introductionmentioning
confidence: 99%